Secondary Brain Injury Following Neonatal Intraventricular Hemorrhage: The Role of the Ciliated Ependyma - Dawes, William (Frontiers in Pediatrics, 2022)
Intraventricular haemorrhage is recognised as a leading cause of hydrocephalus in the developed world and a key determinant of neurodevelopmental outcome following premature birth. Even in the absence of haemorrhagic infarction or posthaemorrhagic hydrocephalus, there is increasing evidence of neuropsychiatric and neurodevelopmental sequelae. The pathophysiology underlying this injury is thought to be due to a primary destructive and secondary developmental insult, but the exact mechanisms remain elusive and this has resulted in a paucity of therapeutic interventions. The presence of blood within the cerebrospinal fluid results in the loss of the delicate neurohumoral gradient within the developing brain, adversely impacting on the tightly regulated temporal and spatial control of cell proliferation and migration of the neural stem progenitor cells within the subventricular zone. In addition, haemolysis of the erythrocytes, associated with the release of clotting factors and leucocytes into the cerebrospinal (CSF), results in a toxic and inflammatory CSF microenvironment which is harmful to the periventricular tissues, resulting in damage and denudation of the multiciliated ependymal cells which line the choroid plexus and ventricular system. The ependyma plays a critical role in the developing brain and beyond, acting as both a protector and gatekeeper to the underlying parenchyma, controlling influx and efflux across the CSF to brain interstitial fluid interface. In this review I explore the hypothesis that damage and denudation of ependymal layer at this critical juncture in the developing brain, seen following IVH, may adversely impact on the brain microenvironment, exposing the underlying periventricular tissues to toxic and inflammatory CSF, further exacerbating disordered activity within the subventricular zone (SVZ). By understanding the impact that intraventricular haemorrhage has on the microenvironment within the CSF, and the consequences that this has on the multiciliated ependymal cells which line the neuraxis, we can begin to develop and test novel therapeutic interventions to mitigate damage and reduce the associated morbidity.